Impact of In‐hospital and Outreach models for regional P.A.R.T.Y. Program participants. (19th December 2020) - McLeod, Janet; Ball, Hayley; Gunn, Anna; Howard, Teresa; Fitzgerald, Mark C; Cameron, Peter A; Mitra, Biswadev
Abstract: Objective: This retrospective observational study aimed to compare the impact of the Prevent Alcohol and Risk‐Related Trauma Youth (P.A.R.T.Y.) Program when delivered as In‐hospital or Outreach models to rural and regional students. Methods: The study population were consented participants from regional areas between 2013 and 2017 who completed pre‐programme, immediately post‐programme and 3–5 months post‐programme surveys. Responses from the metropolitan In‐hospital programme participants and regional Outreach programme participants were analysed within groups across the three time points. The primary outcome variable was a change in self‐reported perception of driving after drinking alcohol. Secondary outcome variables were designating a safe driver after drinking, perception of risk of injury if not wearing a seatbelt, risks of injury if undertaking physical risk‐taking activities and likelihood of the programme changing perceptions. Results: There were 1314 participants invited to participate and 547 (42%) sets of complete surveys were received, of whom 296 (54%) were Outreach participants. Pre‐programme, a significantly lower proportion of Outreach participants reported 'definitely not' to driving after drinking (84% vs 91%), and perceived a 'definite' likelihood of sustaining injury if not wearing a seatbelt (57% vs 66%). Outreach participants displayed improvements in likelihood to drive after drinking alcohol immediately post‐programme and on follow up ( P  = 0.028). Responses to all other secondary outcome measures demonstrated some improvement. Conclusions: Although demographically similar, baseline perceptions toward alcohol, risk‐taking and injury differed between groups. Improvements in perception were demonstrated across both models. These findings support P.A.R.T.Y. as an injury prevention initiative for regional youth. Abstract : The present study aimed to compare the impact of the Prevent Alcohol and Risk‐Related Trauma Youth (P.A.R.T.Y.) Program when delivered as In‐hospital or Outreach models to rural and regional senior school students. Although demographically similar, baseline perceptions toward alcohol, risk‐taking and injury differed between groups. Improvements in perception were demonstrated across both models. These findings support P.A.R.T.Y. as an injury prevention initiative for regional youth.